If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x = 20(2x) Remove parenthesis around (2x) 3x = 20 * 2x Multiply 20 * 2 3x = 40x Solving 3x = 40x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-40x' to each side of the equation. 3x + -40x = 40x + -40x Combine like terms: 3x + -40x = -37x -37x = 40x + -40x Combine like terms: 40x + -40x = 0 -37x = 0 Divide each side by '-37'. x = 0 Simplifying x = 0
| 10.6x+23.87=-9.4x+22.55 | | 8=3x-16 | | 10x=12x-14 | | 3y=-9x-3 | | -3+3x=2x+4 | | 4x-(5+2x)+10=21 | | 1.7-4.9= | | 1/3(12x-6)=-6 | | 16=-40-(-8y-4) | | 23x-20+x+80=180 | | 4+83= | | 3(2-3)=-9 | | 3.6-5= | | 4xy(xy-1)+7xy(xy-3)= | | 3.6n-5n= | | X+x+83+x+11=90 | | y=6x^3-5x^2-17x+6 | | -3/2=7y/2-(-3y/2-3/2) | | 10+2x=-28-33x | | n(180n-360/n)=n(150) | | -2x-(x+5)=2+x-4x-7 | | 9x1/2 | | H(x)=x+4x-7 | | x(x-7)-3x(x+8)= | | 5x-2(3x-3)=17 | | 150-35v=45 | | -3x+6=1x-6 | | -10+.25x=-10 | | 5x-4-5x=-31 | | -10+.25x=-8 | | ax-n= | | 23x-20=x+80 |